2004
DOI: 10.1177/000992280404300809
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Steps: Resident’s Perceptions

Abstract: The objective of this study is to determine pediatric residents' perception of Healthy Steps for Young Children, Healthy Steps Iowa, and Healthy Steps specialists. Twenty-nine of 37 (78%) pediatric residents participated in this survey. The Healthy Steps specialists facilitated pediatric residents' learning of anticipatory guidance (69%), and assured the patients received information efficiently (69%). Sixty-two percent reported that the Healthy Steps specialists did not interfere with their relationship as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Eleven articles were identified through a reference search of accepted articles. Thirty-three articles were accepted; these included 13 articles primarily on alternative formats for WCC, 16,25-36 2 articles primarily on nonclinical locations for WCC, 37,38 17 articles primarily on nonphysicians/ non-NPs added to enhance WCC, 17,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 1 miscellaneous article. 55 Of 13 WCC format articles, 5 were on non-face-to-face formats, [25][26][27][28]36 and 8 were on group visit formats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven articles were identified through a reference search of accepted articles. Thirty-three articles were accepted; these included 13 articles primarily on alternative formats for WCC, 16,25-36 2 articles primarily on nonclinical locations for WCC, 37,38 17 articles primarily on nonphysicians/ non-NPs added to enhance WCC, 17,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 1 miscellaneous article. 55 Of 13 WCC format articles, 5 were on non-face-to-face formats, [25][26][27][28]36 and 8 were on group visit formats.…”
Section: Resultsmentioning
confidence: 99%
“…17,39,40,[45][46][47][48][49] Three articles report data from an extension study at a large integrated health maintenance organization, [41][42][43] and 2 report findings from residency continuity clinics that implemented HS as part of the national program. 44,50 Chart review and parent interview at child age 30 to 33 months revealed that intervention children were more likely to have timely well-child visits (eg, 12-month visit 90% vs 81%, P , .001), be up-to-date on vaccinations at 24 months (83% vs 75%, P , .001), remain at the practice for $20 months (70% vs Outcomes:…”
Section: Nonphysician Providersmentioning
confidence: 99%
“…28 In a separate study, the majority of pediatric residents at a participating site indicated HS increased the efficiency of wellchild visits, and did not detract from their role with parents. 29 When Healthy Steps was integrated as a core component of residency training, residents not only jointly conducted well-child visits with an HS specialist, but also made at least 3 home visits during the first year of their training.…”
Section: Quality Of Care Outcomesmentioning
confidence: 99%
“…This program aims "to enhance and expand preventive pediatrics around developmental, behavioral, and psychosocial issues for families with children 0 to 3 years old" and to aid pediatric practices in promoting child development and family relationships more effectively. 9,10 The central component of this program is a non-physician behavioral/developmental specialist, called a "Healthy Steps Specialist," who provides direct counseling about common B/D issues and anticipatory guidance in the practice setting to families of young children. These specialists are most commonly trained in early childhood education, nursing, social work, or child development.…”
mentioning
confidence: 99%